2014
DOI: 10.1021/am404602t
|View full text |Cite
|
Sign up to set email alerts
|

Using Three-Dimensional 3D Grazing-Incidence Small-Angle X-ray Scattering (GISAXS) Analysis To Probe Pore Deformation in Mesoporous Silica Films

Abstract: In the past decade, remarkable progress has been made in studying nanoscale objects deposited on surfaces by grazing-incidence small-angle X-ray scattering (GISAXS). However, unravelling the structural properties of mesostructured thin films containing highly organized internal three-dimensional (3D) structures remains a challenging issue, because of the lack of efficient algorithms that allow prediction of the GISAXS intensity patterns. Previous attempts to calculate intensities have mostly been limited to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…It should be noted here that unlike in conventional diffraction experiment the form factor P ( q ) decides here the shape of the measured diffraction spot as the dimension of the scattering object is few nanometer wide. Moreover asymmetry in the scattering object can get reflected in the measured shape of the diffraction spots, as shown earlier 43 . In this geometry ( q ) can be considered as resolution function and the distribution of the diffraction spots on the x-ray detector is essentially determined by the structure factor F ( q ) that represents the symmetry of the unit cell.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…It should be noted here that unlike in conventional diffraction experiment the form factor P ( q ) decides here the shape of the measured diffraction spot as the dimension of the scattering object is few nanometer wide. Moreover asymmetry in the scattering object can get reflected in the measured shape of the diffraction spots, as shown earlier 43 . In this geometry ( q ) can be considered as resolution function and the distribution of the diffraction spots on the x-ray detector is essentially determined by the structure factor F ( q ) that represents the symmetry of the unit cell.…”
Section: Methodsmentioning
confidence: 77%
“…The shape evolution of the individual micelle can be intuitively derived from the notion of Curie principle 43 of scattering which stipulates that the symmetry of the measured diffraction spot must be identical to the symmetry of the scatterer. The form factor (refer equation 2 in methods) of the individual micelle plays a defining role in the shape of the observed diffraction spot.…”
Section: Resultsmentioning
confidence: 99%
“…While refl ectometry techniques have been extensively applied to analysis of mineral surfaces (e.g., Fenter et al 2000aFenter et al ,b,c, 2001Cheng et al 2001a;Teng et al 2001;Fenter 2002;Schlegel et al 2002Schlegel et al , 2006Fenter and Sturchio 2004;Geissbuhler et al 2004;Predota et al 2004;Zhang et al 2004Zhang et al , 2006Zhang et al , 2008Park et al 2006;Vlcek et al 2007), experiments using GISAS for analysis of surface experiments and pore precipitation have been more limited (e.g. Jun et al 2010;Fernandez-Martinez et al 2012aDe Yoreo et al 2013;Panduro et al 2014), and we know of none for GISANS. However, these have shown that the potential applications of this technique for analysis of precipitation in pores or on mineral surfaces is signifi cant.…”
Section: Gisasmentioning
confidence: 99%
“…In recent years, GISAXS has emerged as a powerful technique for the structural characterization of the pore arrangement in nanoporous thin films. [18][19][20] Here, it is shown that in situ GISAXS during ALD can be used to monitor the change in density and internal surface area with progressing growth, and hence provide information on the pore filling mechanism. The interpretation of the GISAXS data is discussed based on the results of complementary in situ XRF measurements and a detailed characterization of the original mesoporous film by EP and quantitative electron tomography.…”
Section: Introductionmentioning
confidence: 99%